The Role of Organizational Culture in Shaping Employee Behavior and Performance - Achmad Gani; Serlin Serang; Muh. Aditya A.W; Nesa Safriani (Jurnal Ilmu Manajemen Profitability, 2026)
Organizational culture is a strategic factor that shapes employee behavior and contributes to improved employee performance. However, the effectiveness of organizational culture depends on how cultural values are strengthened, communicated, and internalized through leadership and organizational practices. This study aimed to examine the role of organizational culture in shaping work behavior and employee performance and to identify the role of leadership and organizational culture strengthening strategies in improving employee motivation and performance. The study used a literature review with a descriptive qualitative approach through a systematic review of relevant scientific journals and academic books. The findings indicated that organizational culture had a significant influence on employee performance, both directly and indirectly through increased motivation, job satisfaction, and organizational commitment. The findings also showed that leadership played a key role in shaping and internalizing organizational cultural values, while consistently implemented organizational culture strengthening strategies, including visionary leadership, effective communication of values, and fair reward systems, improved employee motivation and performance. This study contributes theoretically and practically to the development of human resource management by emphasizing the importance of integrating organizational culture, leadership, and strengthening strategies to enhance employee performance. The findings also indicate that a strong organizational culture can support organizational competitiveness and sustainability.